Bacterial analysis of selected sandwich spreads sold in a local market in Manila - Janella G. Redrino. 4 0 16; 5 (2017)
u
Thesis:(B.S. Biology) - Pamantasan ng Lungsod ng Maynila, 2017.
Keywords: 2 -- 0; 6; 20; 20; 2